Upanishadic View Of Pranayama Techniques: A Conceptual Dimension With Special Reference To Yogachudamanyu Upanishad (International Journal of Food and Nutritional Sciences, 2023)
This article has extensively explained Pranayama in the light of the ancient Yoga text Yogachudama Upanishad, other important Hatha Yoga texts and modern scientific research. In this, Pranayama is not limited to breathing process only, but it is presented as a scientific and spiritual practice that leads towards self-realization and Chittavritti-nirodh. The method, benefits, and spiritual elements of Pranayama have been explained in depth in Yogachudama Upanishad, where its goal is to cleanse the nerves, control the mind and attain self-knowledge. Also, through modern research, it has been proved that Pranayama not only provides relief from mental stress, anxiety and diseases, but it also strengthens overall health by having a positive effect on the heart, lungs, nervous system and brain. Thus, this article acts as a bridge between the Yogic tradition and scientific utility of Pranayama, which proves it to be extremely relevant and necessary in contemporary life as well. IntroductionPranayama is such a great tool in Indian Yoga Shastra that it is not only the basis of physical health, but is also a very useful practice in the direction of concentration of mind, purification of nerves and self-realization. The glory of Pranayama has been specially described in Vedas, Upanishads, Mahabharata, Bhagavad Gita and Hatha Yoga texts. Among these texts, "Yogachudramanyupanishad" is a special Upanishad, which is included in the Upanishads focused on Hatha Yoga.